On the Berg-Chen-Ismail Theorem and the Nevanlinna-Pick Problem - Golinskii, L.; Peherstorfer, F.; Yuditskii, P. (Журнал математической физики, анализа, геометрии, 2008)
In 2002, C. Berg, Y. Chen, and M. Ismail found a nice relation between the determinacy of the Hamburger moment problem and asymptotic behavior of the smallest eigenvalues of the corresponding Hankel matrices. We investigate whether an analog of this statement holds for the Nevanlinna-Pick interpolation problem.